Factors determining visitors' willingness to pay for conservation in Yankari Game Reserve, Bauchi, Nigeria - Adamu, Abdullahi; Yacob, Mohd Rusli; Radam, Alias; Hashim, Rohasliney (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
The objective of this study is to examine the factors that determine the local visitors’ willingness to pay (WTP) for conservation in Yankari game reserve, Bauchi, Nigeria. The study employed a dichotomous choice survey design – contingent valuation method (DC-CVM) on 335 local tourists. Binary Logit and Probit models were used to estimate the visitors’ willingness to pay (WTP) for conservation. The empirical results obtained revealed that the game reserve has a considerable use value in that 77.9% of the visitors interviewed are willing to pay for conservation. The results showed that age, gender, income, level of education and first-time visit are the significant determinants of visitors’ willingness to pay. This empirical study would guide not only the management of the game reserve, but also policymakers to consider the important market segment among the visitors with a view to encouraging the visitation of such a target group in order to create an avenue for enhancing revenue for conservation in the game reserve.